2017
DOI: 10.1002/14651858.cd006945.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Urate oxidase for the prevention and treatment of tumour lysis syndrome in children with cancer

Abstract: Although urate oxidase might be effective in reducing serum uric acid, it is unclear whether it reduces clinical TLS, renal failure, or mortality. Adverse effects might be more common for urate oxidase compared with allopurinol. Clinicians should weigh the potential benefits of reducing uric acid and uncertain benefits of preventing mortality or renal failure from TLS against the potential risk of adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 41 publications
(1 reference statement)
0
21
0
1
Order By: Relevance
“…Despite 5 pediatric trials showing a benefit in favor of rasburicase, it was determined that evidence was insufficient to promote the use of rasburicase to prevent TLS or AKI due to the inconclusive findings in a single randomized clinical trial. 19 For our case, there is no evidence to guide a decision on whether or not to use rasburicase. Our case adds to a growing need to conduct randomized trials evaluating the use of rasburicase in both SPTLS and TLS.…”
Section: Discussionmentioning
confidence: 83%
“…Despite 5 pediatric trials showing a benefit in favor of rasburicase, it was determined that evidence was insufficient to promote the use of rasburicase to prevent TLS or AKI due to the inconclusive findings in a single randomized clinical trial. 19 For our case, there is no evidence to guide a decision on whether or not to use rasburicase. Our case adds to a growing need to conduct randomized trials evaluating the use of rasburicase in both SPTLS and TLS.…”
Section: Discussionmentioning
confidence: 83%
“…[67][68][69][70][71] Despite the efficacy of rasburicase in lowering uric acid levels and preventing TLS, it has not been proven to be superior to allopurinol in preventing clinical TLS and related complications. [72][73][74] Despite the lack of data on hard clinical end points, treatment with rasburicase is recommended in all patients with high risk of TLS. The recommended dose of rasburicase is 0.2 mg/kg once daily for up to 5 to 7 days, but lower doses and shorter duration of therapy are commonly used.…”
Section: Tumor Lysis Syndromementioning
confidence: 99%
“…29 Comparative trails between allopurinol and rasburicase have demonstrated more dramatic reductions in serum uric acid and other chemistry markers with rasburicase; however, possibly due to the rarity of clinical TLS, it has been difficult to demonstrate a difference in clinical TLS, renal failure, or mortality. 27,[33][34][35] In a randomized control trial of 52 pediatric patients with leukemia and lymphoma receiving either allopurinol or rasburicase, patients receiving rasburicase had a more rapid decline in uric acid and maintained lower levels of uric acid throughout their therapy, though sample sizes were too small to determine whether this corresponded to a clinical difference in renal outcomes or development of TLS. 27 Another randomized controlled trial compared the efficacy of rasburicase, rasburicase followed by allopurinol, and allopurinol alone in 275 adult patients with hematologic malignancies undergoing chemotherapy.…”
Section: Prevention and Managementmentioning
confidence: 99%
“…33 A Cochrane review on the subject similarly concluded that while rasburicase may be effective in decreasing uric acid, it is unclear whether it is more beneficial than allopurinol in reducing clinical TLS, renal failure, or mortality. 35 With the availability of new hypouricemic agents, further risk classification is required to decide how to pretreat patients undergoing chemotherapy. An expert panel on TLS published a risk classification system that incorporated both hematologic and solid tumor malignancies in 2008, which was further refined in 2010.…”
Section: Prevention and Managementmentioning
confidence: 99%